2017
DOI: 10.12968/hmed.2017.78.9.523
|View full text |Cite
|
Sign up to set email alerts
|

What do doctors and nurses think about development of clinical leadership?

Abstract: Leadership development for health-care professionals is a priority within the NHS. Training is generally targeted at individual staff groups in isolation, even though contemporary leadership thinking recognizes the benefits of collaborative leadership between different clinical disciplines. Focussing on the attitudes and perceived training needs of undergraduate and qualified medical and nursing professionals, this article highlights the similarities and differences and will help to inform the design of existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This enables people to influence change and enhance health systems via education, which is critical since it addresses essential concerns such as interprofessional education, diversity, and ingenuity. 14 The style of leadership has also been shown to influence the commitment and quality of service. A study done in 43 hospitals of Sindh, showed that transformational and transactional leadership styles are positively associated with better commitment and quality of service.…”
Section: Introductionmentioning
confidence: 99%
“…This enables people to influence change and enhance health systems via education, which is critical since it addresses essential concerns such as interprofessional education, diversity, and ingenuity. 14 The style of leadership has also been shown to influence the commitment and quality of service. A study done in 43 hospitals of Sindh, showed that transformational and transactional leadership styles are positively associated with better commitment and quality of service.…”
Section: Introductionmentioning
confidence: 99%